Major vault protein plays important roles in viral infection. Issue 4 (26th November 2019) - Wang, Wei; Xiong, Liang; Wang, Pengyun; Wang, Fubing; Ma, Qingfeng
Abstract: Viral replication and related protein expression inside the host cells, and host antiviral immune responses can lead to the occurrence of diverse diseases. With the outbreak of viral infection, a large number of newly diagnosed and died patients infected with various viruses are still reported every year. Viral infection has already been one of the major global public health issues and lead to huge economic and social burdens. Studying of viral pathogenesis is a very important way to find methods for prevention, diagnosis, and cure of viral infection; more evidence has confirmed that major vault protein (MVP) is closely associated with viral infection and pathogenesis, and this review is intended to provide a broad relationship between viruses and MVP to stimulate the interest of related researchers.